Penggunaan Gambar Luas Daerah untuk Meningkatkan Pemahaman Siswa terhadap Operasi Penjumlahan Bilangan Pecahan Di Kelas V SD Negeri 206 Apala Kabupaten Bone - Ratnah, L Ratnah, L (Universtas Negeri Makassar, 2021)
The initial idea of this research was due to the lack of students' understanding of the addition of fractions, especially students who were unable to add fractions with the shaded area. This is due to the teacher's lack of understanding about learning to add fractions and learning strategies for fractions. The purpose of this study was to improve understanding in adding fractions by using a picture of the area of the fifth grade students of SD Negeri 206 Apala. Data obtained by observation, tests, field notes. The results of this study are that in the first cycle (1) the presentation at the percentage stage in modeling the area image has not been maximized (2) students have difficulty adding fractions (3) group work has not been maximized, while in the second cycle it has shown a significant increase, namely (1 ) the presentation at the percentage stage in modeling the area image has been maximally running according to the plan (2) students feel happy working on the addition of fractions using the area image (3) students can sing the steps for adding fractions using the area image The increase can seen in the first cycle of less qualification (K), the second cycle of good qualification (B). The conclusion of this research is that using the area image in fractional learning can improve the learning outcomes of fifth grade students at SD Negeri 206 Apala .